The role of memory strategies in academic achievement of secondary school students with learning disabilities (2012)
Memory represents a core cognitive or psychological process that enables learners to achieve optimally in their academic pursuits. Without efficient use of memory strategies, students with learning disabilities who have problems with memory may not succeed in their studies. These students may have the ability to process information, but, they do so with great inefficiency. It is a typical far most students with learning disabilities to be unaware of basic strategies that effective learners use in their academic activities. Most authorities recognize that students with learning disabilities have uneven development of cognitive skills. They also agree that the demands of the secondary curriculum can place a strain on the student capacity to attend to the varied sources of input from teachers, instructional materials, and peers. Besides, many educators and psychologists maintain that far effective instruction far students with learning disabilities teachers must understand the flow of information among three types of memory: sensory register, working (short-term) memory, and long-term memory. There is also particular concern about memory and executive function. Teaching implications based on the information model of learning was also discussed Therefore, teachers of student with learning disabilities should ensure that their students acquire and use memory strategies used by efficient learners. If this is done, academic achievement far these students in major subject areas such as reading, mathematics, written expression, speaking and listening will improve.